SINGLE BASE EDITING TOOLS WITH PRECISE ACCURACY (2020)
Provided herein are systems, reagents, methods, and kits that are useful for the targeted editing of nucleic acids, including editing a single site within the genome of a cell or subject, e.g., within the human genome. In some embodiments, fusion proteins of Cas9 and cytosine deaminase domains, are provided. In some embodiments, methods for targeted nucleic acid editing are provided.